2010
DOI: 10.1111/j.1750-3639.2009.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Unique Molecular Characteristics of Pediatric Myxopapillary Ependymoma

Abstract: Myxopapillary ependymoma (MEPN) generally can be cured by gross total surgical resection and usually manifest a favorable prognosis. However, surgery is less curative in tumors that are large, multifocal or extend outside the thecal sac. Late recurrences may occur, particularly in pediatric patients. The role of adjuvant therapy is unclear in the clinical management of recurrent tumors. Clinical trial design requires a better understanding of tumor biology. Unique molecular features of MEPN were investigated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 38 publications
3
52
0
Order By: Relevance
“…Lukashova-v Zangen and colleagues reported 30 genes that were preferentially expressed in subependymomas (spinal and intracranial) as compared to spinal myxopapillary ependymomas (MEPN), including ETV6, YWHAE, TOP2A, TLR2, ADE2H1, IRAK1, TIA1, TTL, UFD1L, TOMM70A and HSD3B1 [62,67]. MEPN are almost exclusively limited to the distal spinal cord [67].…”
Section: Spinal Tumorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lukashova-v Zangen and colleagues reported 30 genes that were preferentially expressed in subependymomas (spinal and intracranial) as compared to spinal myxopapillary ependymomas (MEPN), including ETV6, YWHAE, TOP2A, TLR2, ADE2H1, IRAK1, TIA1, TTL, UFD1L, TOMM70A and HSD3B1 [62,67]. MEPN are almost exclusively limited to the distal spinal cord [67].…”
Section: Spinal Tumorsmentioning
confidence: 99%
“…MEPN are almost exclusively limited to the distal spinal cord [67]. Korshunov and colleagues found that MEPN expressed high amounts of PLA2G5 (1p36-p34) and ITIH2 (10p15), which distinguished MEPN from intracranial ependymomas [3,29,67].…”
Section: Spinal Tumorsmentioning
confidence: 99%
See 3 more Smart Citations